2016
DOI: 10.1074/jbc.m116.756502
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sialylated Glycans in Human Platelet Endothelial Cell Adhesion Molecule 1 (PECAM-1)-mediated Trans Homophilic Interactions and Endothelial Cell Barrier Function

Abstract: Edited by Gerald HartPlatelet Endothelial Cell Adhesion Molecule 1 (PECAM-1) is a major component of the endothelial cell intercellular junction. Previous studies have shown that PECAM-1 homophilic interactions, mediated by amino-terminal immunoglobulin homology domain 1, contribute to maintenance of the vascular permeability barrier and to its re-establishment following inflammatory or thrombotic insult. PECAM-1 glycans account for ϳ30% of its molecular mass, and the newly solved crystal structure of human PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…At 8 and 15 days postinfection, OT‐I CD8 + T cells were sorted and found to have a significant reduction in Pecam‐1 transcripts . Interestingly, CD31 can colocalize with the TGFβ receptor on the cell surface to enhance the suppressive effects of TGFβ . Given that TGFβ levels are elevated in multiple neonatal infection models, it is interesting to speculate that neonatal CTLs would be exquisitely sensitive to TGFβ/CD31‐mediated suppression .…”
Section: Tcr Inhibitory Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…At 8 and 15 days postinfection, OT‐I CD8 + T cells were sorted and found to have a significant reduction in Pecam‐1 transcripts . Interestingly, CD31 can colocalize with the TGFβ receptor on the cell surface to enhance the suppressive effects of TGFβ . Given that TGFβ levels are elevated in multiple neonatal infection models, it is interesting to speculate that neonatal CTLs would be exquisitely sensitive to TGFβ/CD31‐mediated suppression .…”
Section: Tcr Inhibitory Moleculesmentioning
confidence: 99%
“…87 Interestingly, CD31 can colocalize with the TGF receptor on the cell surface to enhance the suppressive effects of TGF . 88 Given that TGF levels are elevated in multiple neonatal infection models, it is interesting to speculate that neonatal CTLs would be exquisitely sensitive to TGF /CD31-mediated suppression. 21,22 Therefore, in addition to differences in TCR structure and avidity, there are inhibitory molecules that regulate the TCR and regulate effector function.…”
Section: The Role Of the Human Public Tcr Repertoirementioning
confidence: 99%
“…PECAM-1 is able to control the activity of platelets, regulate the migration of leukocytes to the vascular intima and maintain the integrity of the vessel wall. If endothelial cells are injured, their function is decreased, leading to adverse consequences (31,32). The results of the present study suggested that PECAM-1 and VCAM-1 may serve important roles in the regulation of endometrial hyperplasia by medical adhesive.…”
Section: Discussionmentioning
confidence: 62%
“…However, carbohydrates part in leukocyte transmigration is still not clear. The recent studies show that N-glycosylation of JAM-A is required for the protein's ability to reinforce barrier function [22]; sialic acid-containing glycan of PECAM-1 reinforces dynamic endothelial cell-cell interactions by stabilizing the PECAM-1 homophilic binding interface [52]; glycosylation status of ICAM-2 (hypo-or non-glycosylated variants) significantly affects the function of this protein in cell motility assays [107]; in pro-inflammatory conditions, modification of VE-cadherin glycans is observed [55]. This obviously requires further investigations.…”
Section: The Glycan-mediated Processes In Inflammationmentioning
confidence: 99%
“…N-glycans of the junctional adhesion molecule-A (JAM-A) regulate leukocyte adhesion and lymphocyte function-associated antigen-1 (LFA-1) binding [22]. Platelet/endothelial cell adhesion molecule-1 (PECAM-1 or CD31), a membrane highly glycosylated protein (~30% of molecular mass), has N-linked glycans represented by neutral and sialylated glycans [51,52]. E-selectin is heavily glycosylated protein with hybrid/complex type N-linked oligosaccharides [53].…”
Section: Introductionmentioning
confidence: 99%